Encapsulation of Hydrogen Peroxide in PVA/PVP Hydrogels for Medical Applications - Natalie Mounayer; Sivan Shoshani; Elena Afrimzon; Taly Iline-Vul; Moris Topaz; Ehud Banin; Shlomo Margel (Gels)
Researchers have been investigating the physical and morphological properties of biodegradable polymer and copolymer films, blending them with other chemicals to solve challenges in medical, industrial, and eco-environmental fields. The present study introduces a novel, straightforward method for preparing biodegradable hydrogels based on polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP) for medical applications. The resulting PVA/PVP-based hydrogel uniquely combines the water absorbency, biocompatibility, and biodegradability of the polymer composite. For hygiene products and medical uses, such as wound healing, hydrogen peroxide (HP) was encapsulated in the PVA/PVP hydrogels for controlled release application. Incorporating PVP into PVA significantly enhances the hydrogel water absorbency and improves the mechanical properties. However, to mitigate the disadvantage of high water absorbency which could result in undesired early dissolution, efforts were made to increase the water resistance and the mechanical characteristics of these hydrogels using freeze–thaw (F/T) cycles and chemical crosslinking PVA chains with trisodium trimetaphosphate (STMP). The resulting hydrogels serve as environmentally friendly bio-based polymer blends, broadening their applications in medical and industrial products. The structural and morphological properties of the hydrogel were characterized using Fourier transform infrared spectroscopy (FTIR), environmental scanning electron microscope analysis (E-SEM), and water-swelling tests. The HP controlled release rate was evaluated through kinetic release experiments using the ex vivo skin model. The antibacterial activity of the hydrogel films was examined on four medically relevant bacteria: Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Pseudomonas aeruginosa, with an adapted disk diffusion assay. Using this assay, we also evaluated the antibacterial effect of the hydrogel films over the course of days, demonstrating the HP controlled release from these hydrogels. These findings support further in vivo investigation into controlled HP release systems for improved wound-healing outcomes.